Prawa człowieka w czasach rywalizacji geopolitycznej XXI wieku - Mik, Cezary (PRAWO i WIĘŹ, 2024)
Human rights are among the recognized areas of international law. However, global actors such as the United States, the European Union, China and Russia have different perceptions of their place in the international order. These differences have been exacerbated as China and Russia have increasingly challenged the dominant position of the United States since the late 20th century. Russia’s aggression against Ukraine and the practical division of the world into the West and East have been of additional importance in exacerbating the differences. The positions of these parties with regard to human rights are presented in the context of the formulation of doctrines of the international order, the attitude towards the attempt to recognize that certain human rights constitute norms juris cogentis, and the relationship between human rights and unilateral coercive measures.